Analysis of cerebral infarction caused by dysplasminogenemia in three pedigrees - Chen, Xuanyu; Zou, Ming; Lu, Chunxing; Zhou, Ruyi; Lou, Shuyue; Wang, Yujia; Ding, Hongxiang; Han, Zhao; Hu, Beilei (Frontiers in Genetics, 2023)
Background and aims: Dysplasminogenemia is a rare heritable disease caused by plasminogen (PLG) gene defects resulting in hypercoagulability. In this report we describe three notable cases of cerebral infarction (CI) complicated with dysplasminogenemia in young patients. Methods: Coagulation indices were examined on STAGO STA-R-MAX analyzer. PLG:A was analyzed using a chromogenic substrate-based approach using a chromogenic substrate method. All nineteen exons of PLG gene and their 5 'and 3' flanking regions were amplified by Polymerase chain reaction (PCR). Suspected mutation was confirmed by reverse sequencing. Results: PLG activity (PLG:A) in proband 1 and 3 of his tested family members, proband 2 and 2 of his tested family members, and proband 3 and her father were all reduced to roughly 50% of normal levels. Sequencing led to the identification of a heterozygous c.1858G>A missense mutation in exon 15 of the PLG gene in these three patients and affected family members. Conclusions: We conclude that the observed reduction in PLG:A was the result of this p.Ala620Thr missense mutation in the PLG gene. The CI incidence in these probands may be attributable to the inhibition of normal fibrinolytic activity as a consequence of this heterozygous mutation.